HIGH-SPEED ONE-AUGER MIXER OF CONTINUOUS ACTION FOR PREPARATION OF SAND-RESIN MIXTURES - D. A. Kudin; S. V. Kudijashov; B. V. Kurakevich (Литьë и металлургия)
The working of high-speed single-auger blender of continuous action for preparation of sand-resin mixtures is described.